2010
DOI: 10.1007/s00244-010-9489-2
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Carbon and Nitrogen Stable Isotopes in Organisms from a Tropical Coastal Lagoon

Abstract: Trace elements (Fe, Mn, Al, Zn, Cr, Cu, Ni, Pb, Cd, Hg, and As) and stable isotope ratios (δ13C and δ15N) were analyzed in sediments, invertebrates, and fishes from a tropical coastal lagoon influenced by iron ore mining and processing activities to assess the differences in trace element accumulation patterns among species and to investigate relations with trophic levels of the organisms involved. Overall significant negative relations between trophic level (given by 15N) and trace element concentrations in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…Thus it is expected that trace element concentrations can be highly variable among different phyla in the environments. Possible explanations for the variability in trace element concentrations include species-specific differences in bioaccumulation dynamics as well as differences in trace element exposure, such as those related to dietary preferences, feeding behaviour, food chain structure, and trophic position [34,35].…”
Section: Downloaded By [Selcuk Universitesi] At 05:53 05 February 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is expected that trace element concentrations can be highly variable among different phyla in the environments. Possible explanations for the variability in trace element concentrations include species-specific differences in bioaccumulation dynamics as well as differences in trace element exposure, such as those related to dietary preferences, feeding behaviour, food chain structure, and trophic position [34,35].…”
Section: Downloaded By [Selcuk Universitesi] At 05:53 05 February 2015mentioning
confidence: 99%
“…Trace elements, whether of natural or anthropogenic origin, are present in all marine ecosystems throughout the world [1]. Some trace elements (Zn, Mn, Cu, Fe, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A tropical coastal lagoon located in Southeast Brazil that receives runoff from iron ore mining and processing activities was studied to assess the differences in trace element accumulation patterns in sediment and to investigate relationships between metal accumulation and trophic status of the organisms (Pereira et al, 2010). Trace element accumulation in biota depended not only on the trophic position of the organisms but also on the functional ecological guilds of the species involved.…”
Section: The Consumers At Riskmentioning
confidence: 99%
“…Because previous studies have shown that some elements, such as Fe and Cu, reached high levels in the livers of fish collected in this lagoon [19], we were interested in finding out what possible associations there might be between Fe (and Cu, Zn, Mn, Al, Cr, Pb, Ni, Cd, As, and Hg) and the antioxidant vitamin A in fish livers.…”
Section: Introductionmentioning
confidence: 98%